Проблемы идентичности в информационную эпоху - Мазур, В. (ХНУРЭ, 2012)
Search of the main features of identity common to all levels of selfdetermination, cultural areas and historical eras. Singularity of virtual environment is the formation of a new ritual definitions of identity. Under the conditions of transition to an information society the problem of defining cultural of identity becomes highly relevant. Electronic communication creates the conditions for broad experimentation of their own identity.